Around the Petit-Chasseur site in Sion (Valais, Switzerland) and new approaches to the Bell Beaker culture : proceedings of the International Conference held at Sion (Switzerland) October 27th-30th, 2011 - Besse, Marie (Archaeopress, 2014)
To commemorate the 50th anniversary of the discovery of the megalithic necropolis of Petit- Chasseur in Sion (Valais, Switzerland), an international conference was organised from the 27th to the 29th of October 2011 in Sion. This book constitutes the conference proceedings.